Analisis Pengelolaan Dokumen di Departemen Pemasaran Kompas Gramedia - Muhammad Bintang Prakoso; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to analyze document management in the Marketing Department of Kompas Gramedia using the case study method and qualitative approach. By collecting primary data from observations, interviews and documentation, as well as secondary data from literature studies, this research identified a number of relevant findings. The research results show that the Kompas Gramedia Marketing Department has successfully implemented an organized document storage and archiving system, both in physical and digital form, with clear labels and categories. This has increased operational efficiency, collaboration and productivity within the department. However, research also reveals several obstacles in document management, such as data input errors, inappropriate document placement, and an excessive number of documents. The proposed solution includes training, system optimization, clear division of tasks, and capacity management to overcome the problem. By implementing these solutions, the Marketing Department can increase the effectiveness of document management, reduce related errors, and maintain smooth operations. In order to increase understanding of the effectiveness of document management in organizational environments, this research provides valuable insights. In addition, the research results can contribute to the field of archives and information management and provide guidance for other organizations facing similar challenges in document management.